Strategi Customer Service Excellence Pada Customer Service B21 Digital Printing Gresik - Saadatul Khoiriyah; Hesty Prima Rini (MESTAKA: Jurnal Pengabdian Kepada Masyarakat, 2024)
In today's competitive era of globalization, customer satisfaction is the key to the success and sustainability of a company. This journal discusses the Customer Service Excellence strategy implemented by B21 Digital Printing, a digital printing industrial company in Indonesia. In this era of digitalization, companies are faced with demands to not only survive, but also innovate in every aspect of operations, especially in understanding and meeting customer needs, carrying out effective communication, and providing good service and handling complaints. Through qualitative research methods, using a qualitative descriptive approach. The research results show that B21 Digital Printing has succeeded in achieving integrated Customer Service Excellence by utilizing technology, by creating software applications, namely the WA CS (WhatsApp Customer Service) and BIMA (Business Integrated Management Apps) applications. The WA CS application provides organization and efficiency in customer service with Chatbots and Artificial Intelligence features for fast response. Meanwhile, the BIMA application makes business operations easier, from ordering to company financial management. With this technological innovation, B21 Digital Printing has succeeded in overcoming several common problems faced in the digital printing industry. In this way, B21 Digital Printing has succeeded in increasing competitiveness, customer loyalty and maintaining customer trust in the company.